PersistOM: an objects-to-multivalued database mapping mechanism - Wei, F.G.; Lee, S.P. (2009)
Most modern business applications today are developed by using object technology such as Java to build application software and using a relational or multivalued database to store data. Nevertheless, impedance mismatch exists between objects and data store mechanisms. Hence, object persistence has become a necessary practice to map database records into objects for further in-memory processing. However, most research works focus on objects to relational database mapping and very few works focus on objects to multivalued database (O/M) mapping. Nonetheless, these few existing O/M mapping mechanisms are either hard to be extended or difficult to be managed. This paper presents the design of an O/M mapping mechanism called PersistOM with design patterns. A set of design patterns has been applied to make the PersistOM easy to be extended and reused. Layers architectural pattern was applied to structure the whole mapping mechanism to ensure each mapping sub-layer is at a particular level of abstraction. Simulation results show that PersistOM not only shortens the overall development period, but also is comparatively easy to be modified and extended.